2008
DOI: 10.1099/vir.0.2008/002857-0
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative mutant cyclin T1 proteins that inhibit HIV transcription by forming a kinase inactive complex with Tat

Abstract: Transcription of the human immunodeficiency virus type 1 (HIV) requires the interaction of the cyclin T1 (CycT1) subunit of a host cellular factor, the positive transcription elongation factor b (P-TEFb), with the viral Tat protein, at the transactivation response element (TAR) of nascent transcripts. Because of this virus-specific interaction, CycT1 may potentially serve as a target for the development of anti-HIV therapies. Here we report the development of a mutant CycT1 protein, containing three threonine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…These findings suggest that regulation of the Tatmediated transcriptional activation of HIV-1 may also involve another mechanisms such as modulation of Tat stability 23 and its association with negative factors. 16 Although the RXL motif in most of the CDK/ cyclin substrates such as p24 and p21 is known to play a key role, 24,25 and the target Arg is recognized by Glu on the first helix of cyclin A, the interaction between CycT1 and Tat appears to use a distinct amino acid interaction. However, Tahirov et al 18 showed that Asp (D) at amino acid 47 of CycT1 binds to Tyr (Y) at amino acid 47 of Tat.…”
Section: Transcriptional Activity Of the Cyct1-tat Chimera Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that regulation of the Tatmediated transcriptional activation of HIV-1 may also involve another mechanisms such as modulation of Tat stability 23 and its association with negative factors. 16 Although the RXL motif in most of the CDK/ cyclin substrates such as p24 and p21 is known to play a key role, 24,25 and the target Arg is recognized by Glu on the first helix of cyclin A, the interaction between CycT1 and Tat appears to use a distinct amino acid interaction. However, Tahirov et al 18 showed that Asp (D) at amino acid 47 of CycT1 binds to Tyr (Y) at amino acid 47 of Tat.…”
Section: Transcriptional Activity Of the Cyct1-tat Chimera Proteinsmentioning
confidence: 99%
“…13,15 In addition, three Thr residues, T143, T149 and T155, in CycT1 were shown to be important for Tat action. 16 When all three Thr residues were substituted by Ala, although the formation of the Tat-TAR-P-TEFb complex was not hampered, the Tat-mediated transactivation was greatly diminished presumably through binding of negative regulators. 16 Furthermore, it was shown that the N-terminal region of CycT1 containing amino acids 67-71 was crucial for Tat transactivation.…”
Section: Introductionmentioning
confidence: 99%
“…101 DRB successfully blocked Tat-activated transcriptional elongation in vitro and Tat transactivation in cell culture. 102 The use of smallmolecular-weight compounds or mutant proteins to impair cyclin-dependent kinases activities [103][104][105][106] or use of antihCycT1 human single chain antibodies 107 could also abrogate HIV-1 replication. CDK inhibitors highly selective against CDK9 appear to be desirable but still require further investigations.…”
Section: Tatmentioning
confidence: 99%
“…Several non-small-molecule inhibitors have been explored such as cyclin T1 intrabodies (Bai et al 2003), microRNA-198 (Sung and Rice 2009), cyclin T1-dominant negative mutants (Jadlowsky et al 2008a, b), and the overexpression of HEXIM1/2 (Fraldi et al 2005). Recently, an in silico screening targeting the Tat/TAR RNA recognition motif of cyclin T1 identified the compound C3 , which inhibits association of cyclin T1/Tat, as well as Tat-mediated LTR transcription in a reporter assay (Fig.…”
Section: Inhibition Of P-tefb An Essential Cellular Complex For Himentioning
confidence: 99%